2019
DOI: 10.1111/joim.12994
|View full text |Cite
|
Sign up to set email alerts
|

Associations between chronotype, MTNR1B genotype and risk of type 2 diabetes in UK Biobank

Abstract: ObjectiveTo examine the association between the MTNR1B G risk allele, type 2 diabetes (T2D) and chronotype in the UK Biobank.MethodsData from the baseline investigation of the UK Biobank were utilized (n = 337 083 White British; mean age: 56.9 years; 54% women). MTNR1B rs10830963 was directly genotyped [CC (reference group), CG and GG]. Chronotype was divided into four categories: definitely morning (reference group); more morning than evening; more evening than morning; and definitely evening. Logistic regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 21 publications
1
31
0
2
Order By: Relevance
“…MT1/MT2 has been widely studied in glucose metabolic disorders. The polymorphism of the MTNR1B locus encoding MT2 in humans has a strong correlation with impaired insulin secretion and elevated fasting blood glucose [ 111 ]. Clear evidence has also shown the critical role of MT1 in regulating glucose homeostasis in rodents.…”
Section: Potential Mechanisms Of Melatonin In Obesitymentioning
confidence: 99%
“…MT1/MT2 has been widely studied in glucose metabolic disorders. The polymorphism of the MTNR1B locus encoding MT2 in humans has a strong correlation with impaired insulin secretion and elevated fasting blood glucose [ 111 ]. Clear evidence has also shown the critical role of MT1 in regulating glucose homeostasis in rodents.…”
Section: Potential Mechanisms Of Melatonin In Obesitymentioning
confidence: 99%
“…A study of 1014 non-shift working adults in Bangkok with prediabetes reported a significant association between late chronotype and higher HbA1c levels [ 13 ]. A recent study from the UK Biobank also showed that late chronotype increased the risk of T2DM [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals are often classified as "Morning" chronotypes or "Evening" chronotypes, etc. Chronotype is genetically codetermined and has been associated with risk of various negative health endpoints, including DM in the UK Biobank (Archer et al 2018;Erren and Lewis 2019;Roenneberg et al 2003;Tan et al 2020). Chronotype and other timing characteristics of the CTS can differ by ethnicity, sex, and age (Archer et al 2018;Eastman et al 2015;Erren and Lewis 2019;Roenneberg et al 2003).…”
Section: Introductionmentioning
confidence: 99%